Explorative Research On The Connotative Development Of Undergraduate Volunteer Teaching Assistance Services ; A Case Study Of Nanjing Xiaozhuang University - Shen Ping; Wang Jing (Universitas Internasional Batam, 2021)
Volunteer teaching support services have become an essential form of social practice activities for college students in China and have a positive and far-reaching impact on volunteers, recipients, and society as a whole. This article mainly focuses on the college student volunteer service of Nanjing XiaoZhuang University and uses Tao Xingzhi's educational philosophy to illustrate the fundamental characteristics of the connotative development of college student volunteer service. To propose the realization path of the connotative development of college students' voluntary service for supporting education: four-in-one long-term mechanism for supporting education practice and education of